La reforma de la imposición sobre la renta : un informe de 1976 / Dionisio Martínez Martínez ; prólogo de Francisco Fernández Ordóęz - Fernández Ordóęz, Francisco (1930-1992); Martínez Martínez, Dionisio
Bibliografía: p. 127-143